Mujeres de todos los colores de la tierra: En defensa del territorio, los derechos étnicos y de género - Tapia González, Georgina Aimé (Investigaciones Feministas (Feminist Research), 2010)
Original ethnic populations live marginalized by poverty, discrimination and plundering. In the middle of these circumstances, women raise their voices to demand autonomy, health, education, their right to land, the preservation of natural resources and, along with men, to set out gender claims. In this article I will deal particularly with Neo-Zapatista movement in Mexico, which proposes alternative feminist and ecological practices in view of racist, sexist and the ecocide development of neoliberal globalization.
Keywords: Indigenous Women; Neo-Zapatismo; Gender; Ethnic Group; Ecofeminism